ACHIEVEMENT OF MINIMUM EDUCATION SERVICE STANDARDS FOR INDONESIA DURING THE COVID 19 TRANSITION PERIOD - Endang Iryani (Research and Development Journal of Education, 2023)
The emergence of the Covid 19 virus in 2019 has presented a big challenge for local governments in carrying out compulsory education affairs through the achievement of the Minimum Service Standards (SPM) in 2020. So, in 2020, the government made several policies in handling Covid 19, one of which is refocusing the budget from a predetermined budget. The purpose of this study was to see the achievement of the Education (SPM) in 2020 during the Covid 19 transition in the South Tangerang City Government, through a qualitative case study method with the CIPP approach model. The results showed that the South Tangerang City Government had succeeded in achieving two targets for Minimum Service Standards (SPM) for Education in 2020 (the indicators for Basic Education and Equality Education), by implementing performance effectiveness and changing the budget structure in the third quarter after budget refocusing. The achievement indicators for Early Childhood Education (PAUD) were not on target because the people of South Tangerang choose PAUD schools in Jakarta as their place of work. The conclusion from the research was that the South Tangerang City Government has succeeded in carrying out work effectiveness during the COVID-19 transition by refocusing the budget through the effectiveness of employee performance and replanning the 2020 work program